Faktor terauputik konseling realitas dalam proses konseling kelompok - Julia Eva Putri; Neviyarni Suhaili; Yeni Karneli; Netrawati Netrawati (Indonesian Institute for Counseling, Education and Theraphy, 2023)
One theory that can be applied in group counseling is Reality Therapy with an emphasis on connections and interpersonal relationships, which is very suitable for various types of group counseling. Reality therapy is a system that focuses on current behavior, this counseling serves to help counselees face reality and meet basic needs without harming themselves or other individuals. Group counseling with a reality therapy approach, the most important thing is to foster responsibility (responsibility) and awareness of the client. Humans are basically creatures who are responsible for their behavior and fulfillment of their needs. The emphasis on what group members do is key to reality counseling as a counseling group.